A Survey to Capture the Mobility Behavior of Residents in the Republic of Cyprus - Fayad, Philip; Kyriakidis, Phaedon; Tsioutis, Constantinos; Kavroudakis, Dimitris (My University, 2024)
In today's highly mobile world, people of all age groups constantly move between various locations, such as their homes, grocery stores, schools, and workplaces, reflecting the dynamic nature of modern society. The recent COVID-19 pandemic has underscored the profound impact of human mobility on the rapid spread of the virus within and between urban areas. The current study investigates the daily mobility behaviors of residents of the Republic of Cyprus. Through a comprehensive survey, the research documents travel patterns, commuting habits, and transportation preferences across various age groups and districts of Cyprus. With a total of 787 responses from all districts of Cyprus, data was collected through an online survey from 20/11/2023 to 20/02/2024. Data analysis includes descriptive methods and statistical modeling techniques in order to provide insights into the patterns of human mobility. Key findings include insights into travel distances, frequencies, duration and means of transportation, and timelines of mobility activities during typical workdays, as well as during weekends.
Keywords: survey; mobility behavior; urban mobility patterns; spatiotemporal transportation; Cyprus